2021
DOI: 10.3389/fenvs.2021.769067
|View full text |Cite
|
Sign up to set email alerts
|

Role of Renewable Energy Consumption and Technological Innovation to Achieve Carbon Neutrality in Spain: Fresh Insights From Wavelet Coherence and Spectral Causality Approaches

Abstract: This research offers a new perceptive of the dynamic connection between CO2 and globalization, technological innovation (TI), economic growth, and renewable energy (REN) consumption in Spain. The current research applied the wavelet tools to assess these interconnection utilizing data stretching from 1980 to 2018. The outcomes of these analyses disclose that the association among the series evolves over frequency and time. The current analysis uncovers notable wavelet coherence and strong lead and lag connecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…As regards the policy side, the study suggests that any initiative that targets human capital, RDE, economic globalization, and TIN eventually affects green growth. The technologies ensuring green innovations are considered vital for reducing the efficiency and sustainability of energy usage (Anwar & Malik, 2021; Chen et al, 2021; Habiba et al, 2022; Sohag et al, 2015; Zhao et al, 2021). According to Sohag, Taşkın, and Nasir (2019), lnGRN is an effective tool to encourage sustainable economic growth.…”
Section: Theoretical Underpinning and Literature Reviewmentioning
confidence: 99%
“…As regards the policy side, the study suggests that any initiative that targets human capital, RDE, economic globalization, and TIN eventually affects green growth. The technologies ensuring green innovations are considered vital for reducing the efficiency and sustainability of energy usage (Anwar & Malik, 2021; Chen et al, 2021; Habiba et al, 2022; Sohag et al, 2015; Zhao et al, 2021). According to Sohag, Taşkın, and Nasir (2019), lnGRN is an effective tool to encourage sustainable economic growth.…”
Section: Theoretical Underpinning and Literature Reviewmentioning
confidence: 99%
“…The wavelet-based approach is a relatively new area of human knowledge, which is found to be useful for decomposing signals that have a cyclical behavior. In this study, the Morlet wavelet function is employed since it offers good results in terms of balance between time and frequency (Magazzino and Mutascu, 2019;Zhao et al, 2021) and it can be specified as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Where the p(n) which is the time-series data is incorporated. The local variance was revealed using the wavelet power spectrum (WPS) (Zhao et al, 2021). A cone of influence is considered to illustrate the edge effects of the observations.…”
Section: Methodsmentioning
confidence: 99%
“…According to Ozturk et al [20], a positive linkage is found between environmental degradation and EF. The prime determinant of EF is GDP [21], while other determinants are renewable and non-renewable energy, the latter of which is the prime cause of GHG emissions [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%